2018
DOI: 10.1002/pri.1720
|View full text |Cite
|
Sign up to set email alerts
|

Expiratory muscle strength and functional exercise tolerance in adults with cystic fibrosis: a cross‐sectional study

Abstract: Increased functional exercise tolerance is related to higher static expiratory pressure in patients with mild-to-normal cystic fibrosis lung disease. Difference in exercise performance might reflect a possible difference in body composition that needs to be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A relationship between MEP and 6MWD (r = 0.60) has previously been described in children with CF and may explain the low 6MWD [35]. A recently described cohort of adults with CF (MEP 77% predicted value) similarly reported that those with lower MEP had poorer functional exercise capacity [36]. However, explanations underlying this observation are still unclear since other studies have reported differing results [37,38].…”
Section: Plos Onementioning
confidence: 86%
“…A relationship between MEP and 6MWD (r = 0.60) has previously been described in children with CF and may explain the low 6MWD [35]. A recently described cohort of adults with CF (MEP 77% predicted value) similarly reported that those with lower MEP had poorer functional exercise capacity [36]. However, explanations underlying this observation are still unclear since other studies have reported differing results [37,38].…”
Section: Plos Onementioning
confidence: 86%
“…In contrast, another study that evaluated the performance of children and adults with CF in the 6MWT and MSWT found a correlation between respiratory muscle strength and performance in both tests (Saglam et al., 2016). In adults with CF, MEP is related to increased exercise tolerance assessed by the 6MWT (Gambazza et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, children with CF over 8 years of age with a V ̇O2max of < 32 ml•kg -1 •min -1 have 60% increased mortality rate (Pianosi et al, 2005). Although participants in the current study had an average V ̇O2max of 36 ml•kg -1 •min -1 at baseline, higher than the aforementioned high-risk category threshold, eight weeks of IMT still significantly increased their V ̇O2max (Cunha et al, 2006;Gambazza et al, 2018). This discrepancy may be related to inter-study differences in the measurement of exercise capacity.…”
Section: Discussionmentioning
confidence: 56%